2018
DOI: 10.11594/jtls.08.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antimicrobial Screening of Native Plant Swertia chirayita (Roxb. ex Fleming) Karst from Rasuwa district of Nepal

Abstract: Swertia chirayita is one of the highly traded medicinal plants of Nepal. This plant was chosen for investigation as folk medicines and then collected from the diverse habitats of Rasuwa district of Nepal and specimens have been checked and identified at National Herbarium and Plant Laboratories (NHPL), Godavari, Lalitpur. The identified plant was subjected to study physiochemical and biological activity. The stem, root and leaves of the plant were dried, made powder and mixed at the ratio of 1 : 1 : 1 and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous studies indicated that S chirata promisingly exhibited antibacterial properties. 36 , 37 S chirata showed maximum inhibition against the P aeruginosa, K pneumonia, S aureus , and E faecalis . 38…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies indicated that S chirata promisingly exhibited antibacterial properties. 36 , 37 S chirata showed maximum inhibition against the P aeruginosa, K pneumonia, S aureus , and E faecalis . 38…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies indicated that S chirata promisingly exhibited antibacterial properties. 36,37 S chirata showed maximum inhibition against the P aeruginosa, K pneumonia, S aureus, and E faecalis. 38 In our study, C reflexa showed maximum inhibition zone (5 mm) against B subtilis as compared with others.…”
Section: Discussionmentioning
confidence: 95%
“…Leaf and stem showed positive result in most of the phytochemical analysis, except saponins. The study conducted by Subedi, et al (2018) [19] showed negative result in the saponin from leaf and stem of Swertia chirata.…”
Section: Swertia Chiratamentioning
confidence: 94%